LKB1 acts as a critical gatekeeper of ovarian primordial follicle pool - Jiang, Zong-Zhe (Oncotarget, 2015)
Liver Kinase b1 (LKB1/STK11)is a tumor suppressor responsible for the Peutz-Jeghers syndrome, an autosomal-dominant, cancer-prone disorder in which patients develop neoplasms in several organs, including the oviduct, ovary, and cervix. Besides, the C allele of a SNP in the Lkb1 gene impedes the likelihood of ovulation in polycystic ovary syndrome (PCOS) in women treated with metformin, a known LKB1-AMPK activator. It is very likely that LKB1 plays roles in female fertility. To identify the physiological functions of LKB1 in the mouse ovary, we selectively disrupted LKB1 in oocytes by the Cre-LoxP conditional knockout system and found that Lkb1(fl/fl); Gdf9-Cre mice were severely subfertile with significantly enlarged ovaries compared to Lkb1(fl/fl) mice. Interestingly, without Lkb1 expression in oocytes from the primordial follicle stage, the entire primordial follicle pool was activated but failed to mature and ovulate, subsequently causing premature ovarian failure (POF). Further investigation demonstrated that elevated mTOR signaling regulated by an AKT-independent LKB1-AMPK pathway was responsible for the excessive follicle activation and growth. Our findings reveal the role of LKB1 as an indispensable gatekeeper for the primordial follicle pool, offer new functional understanding for the tumor suppressor genes in reproductive organs, and might also provide valuable information for understanding POF and infertility.